UV-Visible Spectrophotometric Determination of Ni(II) Using a Schiff Base Ligand Derived from 1,5-Diphenylcarbazone and Aniline - Moyna Clara L.A., Cindy; Septiani Pratama , Dian; Hidayat , Dicky (Indonesian Journal of Chemical Analysis (IJCA), 2026)
UV-Visible spectrophotometric approach for Ni(II) determination was developed using a Schiff base ligand synthesized from 1,5-diphenylcarbazone and aniline. The ligand was isolated with a yield of 64.98% and exhibited absorption bands at 239 and 278 nm, confirming the formation of the azomethine group. Ni(II) complexation at a metal to ligand molar ratio of 1:3 was carried out through complex formation without crystallization and with crystallization, affording a solid complex with a 57.11% yield. The complex formed without crystallization showed a maximum absorbance at 532 nm, whereas the crystalline complex exhibited a maximum absorbance at 535 nm, indicating identical chromophoric behavior in solution. Coordination was additionally verified by FTIR, as evidenced by the shift of the C=N stretching band toward lower wavenumbers and the emergence of characteristic Ni–N vibrations. The maximum analytical response was obtained at pH 6, and the absorbance remained stable for at least 120 min, demonstrating sufficient complex stability for routine measurements. The addition of Co(II) did not result in statistically significant changes in absorbance, confirming negligible interference under the studied conditions. Overall, the Ni(II)-Schiff base system provides a reproducible and selective spectrophotometric response suitable for nickel determination in aqueous media.